2017
DOI: 10.1177/0091552117716771
|View full text |Cite
|
Sign up to set email alerts
|

Developing Transfer Pride: An Exploration of Critical Race Pedagogy and the Summer Transfer Enrichment Program

Abstract: Objective: This study examined the critical race pedagogy of the Summer Transfer Enrichment Program (STEP) over a 5-year span and how the curriculum and supplemental academic programming aided in the development of a positive transfer identity for its participants. Method: A mixed method convergent parallel design approach was used to collect quantitative and qualitative data in the forms of surveys and focus groups. Fifty-six students, the majority Latinx, responded to the survey along with 22 students in foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Future research may benefit from understanding whether the challenges expressed by participants as transfer students are experienced more often by Latinx and other students of color. It is possible as Jain et al (2017) found and alluded to by Reyes (2011) and Castro and Cortez (2017) that some of the experiences that students perceive as transfers may be connected to their racialized experience as students of color. The present study showed that transfer status exacerbates the challenges Latinx students experience in adjusting to the university.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research may benefit from understanding whether the challenges expressed by participants as transfer students are experienced more often by Latinx and other students of color. It is possible as Jain et al (2017) found and alluded to by Reyes (2011) and Castro and Cortez (2017) that some of the experiences that students perceive as transfers may be connected to their racialized experience as students of color. The present study showed that transfer status exacerbates the challenges Latinx students experience in adjusting to the university.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should also investigate the spaces that validate or create a positive sense of belonging for Latinx transfer students. For example, Andrade (2018) has shed light on the spatial awareness of physical safe spaces for Latinx transfer students and Jain et al (2017) on how critical race pedagogy can be integrated with transition and outreach programs. Finally, more needs to be understood about how university and community colleges manage course alignment between academic departments.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both articles that do use Latinx had Dimpal Jain as a co‐author. Of these two articles, only one defined the term Latinx (Jain, Lucero, Bernal, Herrera, & Solórzano, ) and this article cited Castro and Cortez's () definition as the basis for their usage of the term.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the benefits of transfer support programs specifically designed to aid underrepresented, racially minoritized students' transition from CCs to universities (Dowd et al, 2013;Jackson & Laanan, 2015), collaborations with existing STEM support programs targeting these populations can provide more holistic support within their respective STEM disciplines throughout the transfer process (Herrera & Rodriguez-Operana, 2020;Herrera et al, 2020). Akin to the value of providing culturally relevant STEM curricula, some researchers also argue in favor of incorporating critical race pedagogy within campus programming for transfer students (e.g., Summer Transfer Enrichment Program; Jain et al, 2017), which can provide a safe space to prepare underrepresented and minoritized students to recognize, name, and confront the racism/sexism they may experience within STEM environments (Villasenor et al, 2021).…”
Section: Implications and Future Directionsmentioning
confidence: 99%